Design of Automatic Carriage Doorstop With Arduino: Design of Automatic Carriage Doorstop With Arduino - Resa Wahyu Adi Pujianto; Septi Andryana; Ira Diana Sholihati (Jurnal Mantik, 2020)
The train is a means of transportation that is still in demand by most of the population of Indonesia at this time. But the contribution of the railway itself to national transportation is still very low, accidents because this transportation often occurs because there is still insufficient infrastructure and facilities. Accidents due to trains in general often occur at the doorway of railway crossing this can be caused by the negligence of the officers or attitudes of the other riders who are still very undisciplined. Thus the author finds an idea or idea to create an automatic doorway system. The design in this prototype is by using the pro-tower servo motor, project Board Mini, and the SR-04 ultrasonic sensor, which will be processed with the Arduino UNO microcontroller.